Role of Epithelial-Mesenchymal Transition in Retinal Pigment Epithelium Dysfunction - Zhou, Mi; Geathers, Jasmine S.; Grillo, Stephanie L.; Weber, Sarah R.; Wang, Weiwei; Zhao, Yuanjun; Sundstrom, Jeffrey M. (Frontiers in Cell and Developmental Biology, 2020)
Retinal pigment epithelial (RPE) cells maintain the health and functional integrity of both photoreceptors and the choroidal vasculature. Loss of RPE differentiation has long been known to play a critical role in numerous retinal diseases, including inherited rod-cone degenerations, inherited macular degeneration, age-related macular degeneration, and proliferative vitreoretinopathy. Recent studies in post-mortem eyes have found upregulation of critical epithelial-mesenchymal transition (EMT) drivers such as TGF-β, Wnt, and Hippo. As RPE cells become less differentiated they begin to exhibit the defining characteristics of mesenchymal cells, namely, the capacity to migrate and proliferate. A number of preclinical studies, including animal and cell culture experiments, also have shown that RPE cells undergo EMT. Taken together, these data suggest that RPE cells retain the reprogramming capacity to move along a continuum between polarized epithelial cells and mesenchymal cells. We propose that movement along this continuum toward a mesenchymal phenotype be defined as RPE Dysfunction. Potential mechanisms include impaired tight junctions, accumulation of misfolded proteins and dysregulation of several key pathways and molecules, such as TGF-β pathway, Wnt pathway, nicotinamide, microRNA 204/211 and extracellular vesicles. This review synthesizes the evidence implicating RPE undergoing EMT in post-mortem eyes, animal studies, primary RPE, iPSC-RPE and ARPE-19 cell lines.